“I swear to fight for a free and mighty Poland, carry out the orders of my superiors, so help me God.”Jews in the Home Army. An Episode from Ostrowiec Świętokrzyski - Dariusz Libionka; Alina Skibińska (Zagłada Żydów)
The article presents a selection of documents from a 1949 trial, which concluded with the sentence of three ZWZ-AK members, Opatów district, by the Court of Appeals in Kielce – Józef Mularski, Leon Nowak and Edward Perzyński – for complicity in the murder of 12 Jews from the Ostrowiec Świętokrzyski ghetto in a forest near Kunów. Two of them, severely wounded, returned to the ghetto; one of them survived the war (Szloma Icek Zweigman), and after emigration submitted a detailed and extensive testimony regarding the incident. Zweigman’s testimony was the foundation of the investigation and the indictment. Mularski and Nowak, sentenced to death, were subsequently pardoned and released from prison after 1956, as was the third convict. The case was closed as follows: sentence of 1957 to pardon Józef Mularski, followed by another verdict of 2000 that provided for a high compensation. The presented materials are not only proof that members of the Polish underground committed crimes against Jews, but also demonstrate how the Polish judiciary and the Main Commission to Investigate Nazi Crimes in Poland operated. The latter clearly conducted a policy of papering over those criminal cases in which Poles were the perpetrators. The issues raised in the article are inadequately researched, not only in Polish historiography. The presented trial materials come from the Archives of the Institute of National Remembrance